Chinese Coint in Bali: Historical, Religious and Touristic Perspective - I Made Sendra (International Journal of Interreligious and Intercultural Studies, 2023)
From the historical perspective, China and Bali had a millennium cultural diplomatic relationship. This evident can be seen from tangible and intangible cultural heritage, such as Chinese coin, folklore, architecture of temple etc which represent the cultural acculturation between Bali and China. Due to the booming of Chinese tourist visiting Bali from 2015-2019 the stakeholder in tourism utilized the Bali-China cultural heritage as tourism attraction. The Chinese coin was used by Balinese people as religious artefact on Hindu religion as the prominent element of the offering and became the tourism attraction for Chinese tourists and also as souvenirs as well.This research used the theory of “commodification of the past” from GJ Asworth (1991) to explain the function and the meaning of Chinese coin not only for religious artefact but also touristic function. The collecting data used observation, structured-interview, and library research. The data analysis used qualitative data analysis from Miles and Huberman (in Sugiyono,2011). The data analysis involved some procedure, such as data collection, data reduction, data presentation, and conclusion. The research show that by using the intrinsic and extrinsic interpretation it can explain the intrinsic value (historical religious perspective) and extrinsic value (touristic perspective). The intrinsic value of the utilizing the Chinese coin in Hindu religion due the function and the meaning as cultural artifact. And the extrinsic value is the using of Chinese coin as cultural artifact could has the new meaning as tourism attraction by creating the storynomic to build the emotional attachment, the place attachment, and the social bond between China and Bali which had cultural diplomatic relationship.